OCD behavior therapy before and after gamma ventral capsulotomy: Case report - Spofford, Christopher M. (Neurocase, 2012)
We report the case of a patient requiring gamma ventral capsulotomy (GVC), a neurosurgical intervention to address severe refractory obsessive–compulsive disorder (OCD). GVC involves stereotactic lesions in the ventral anterior limb of the internal capsule and adjacent ventral striatum. This study details the course of an extinction-based behavioral therapy, namely exposure and response prevention (ERP). The patient experienced significant changes in motivation and ability to tolerate ERP post-surgery. Furthermore, he was better able to absorb and remember exposure sessions. GVC surgery may affect the neural mechanisms involved in the extinction learning process, the same process implicated in ERP treatment.